Information and empire mechanisms of communication in Russia, 1600-1850 - Bowers, Katherine; Franklin, Simon; Open Book Publishers (Open Book Publishers, 2017)
"From the mid-sixteenth to the mid-nineteenth century Russia was transformed from a moderate-sized, land-locked principality into the largest empire on earth. How did systems of information and communication shape and reflect this extraordinary change? Information and Empire brings together a range of contributions to shed some light on this complex question. Communication networks such as the postal service and the gathering and circulation of news are examined alongside the growth of a bureaucratic apparatus that informed the government about its country and its people. The inscription of space is considered from the point of view of mapping and the changing public 'graphosphere' of signs and monuments. More than a series of institutional histories, this book is concerned with the way Russia discovered itself, envisioned itself and represented itself to its people. Innovative and scholarly, this collection breaks new ground in its approach to communication and information as a field of study in Russia. More broadly, it is an accessible contribution to pre-modern information studies, taking as its basis a country whose history often serves to challenge habitual Western models of development. It is important reading not only for specialists in Russian Studies, but also for students and non-Russianists who are interested in the history of information and communications. "--Publisher's website.
Acknowledgments -- Notes on Contributors -- Introduction / Simon Franklin -- I. MAP-MAKING. 1. Early Mapping: The Tsardom in Manuscript / Valerie Kivelson -- 2. New Technology and the Mapping of Empire: The Adoption of the Astrolabe / Aleksei Golubinskii -- II. INTERNATIONAL NEWS AND POST. 3. Muscovy and the European Information Revolution: Creating the Mechanisms for Obtaining Foreign News / Daniel C. Waugh and Ingrid Maier -- 4. How Was Western Europe Informed about Muscovy? The Razin Rebellion in Focus / Ingrid Maier -- III. NEWS AND POST IN RUSSIA. 5. Communication and Obligation: The Postal System of the Russian Empire, 1700-1850 / John Randolph -- 6. Information and Efficiency: Russian Newspapers, ca.1700-1850 / Alison K. Smith -- 7. What Was News and How Was It Communicated in Pre-Modern Russia? / Daniel C. Waugh -- IV. INSTITUTIONAL KNOWLEDGE AND COMMUNICATION. 8. Bureaucracy and Knowledge Creation: The Apothecary Chancery / Clare Griffin -- 9. What Could the Empress Know About Her Money? Russian Poll Tax Revenues in the Eighteenth Century / Elena Korchmina -- 10. Communication and Official Enlightenment: The Journal of the Ministry of Public Education, 1834-1855 / Ekaterina Basargina -- V. INFORMATION AND PUBLIC DISPLAY. 11. Information in Plain Sight: The Formation of the Public Graphosphere / Simon Franklin -- 12. Experiencing Information: An Early Nineteenth-Century Stroll Along Nevskii Prospekt / Katherine Bowers -- Selected Further Reading -- List of Figures -- Index.
Available through Open Book Publishers.
Includes bibliographical references (pages 409-416) and index.
Mode of access: World Wide Web.
Keywords: Communication in politics -- Russia -- History; Communication -- Russia -- History; Postal service -- Russia -- History; Press -- Russia -- History; Written communication -- Russia -- History; Russia -- Politics and government -- History; Russia -- Social life and customs -- History